Factors governing success in competitive swimming: A brief review of related studies - Cureton, T. K. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
In the time of Duke Kahanamoku's swimming (1905-1928) the training procedures for competitive swimming were rather indefinite and hardly deserved the connotation of "scientific training." There was little specialization up to 880 yards, as most good swimmers competed over the entire range, and usually in several events. Johnny Weismuller held almost all of the freestyle records, with Jamison Handy and Perry McGillivray holding the middle distance titles, and Bob Skelton holding the breaststroke titles. Girls were not yet accepted in hard training camps, and physiological analysis of swimming and training methods for competition were vague, in fact almost nonexistent.